Organic farming fosters agroecosystem functioning in Argentinian temperate soils: Evidence from litter decomposition and soil fauna - Domínguez, Anahí (2014)
Benefits of organic farming on soil fauna have been widely observed and this has led to consider organic farming as a potential approach to reduce the environmental impact of conventional agriculture. However, there is still little evidence from field conditions about direct benefits of organic agriculture on soil ecosystem functioning. Hence, the aims of this study were to compare the effect of organic farming versus conventional farming on litter decomposition and to study how this process is affected by soil meso- and macrofauna abundances. Systems studied were: (1) organic farming with conventional tillage (ORG), (2) conventional farming with conventional tillage (CT), (3) conventional farming under no-tillage (NT), and (4) natural grassland as control system (GR). Decomposition was determined under field conditions by measuring weight loss in litterbags. Soil meso- and macrofauna contribution on decomposition was evaluated both by different mesh sizes and by assessing their abundances in the soil. Litter decomposition was always significantly higher after 9 and 12 months in ORG than in CT and NT (from 2 to 5 times in average), regardless decomposer community composition and litter type. Besides, mesofauna, macrofauna and earthworm abundances were significantly higher in ORG than in NT and CT (from 1.6 to 3.8, 1.7 to 2.3 and 16 to 25 times in average, respectively for each group). These results are especially relevant firstly because the positive effect of ORG in a key soil process has been proved under field conditions, being the first direct evidence that organic farming enhances the decomposition process. And secondly because the extensive organic system analyzed here did not include several practices which have been recognized as particularly positive for soil biota (e.g. manure use, low tillage intensity and high crop diversity). So, this research suggests that even when those practices are not applied, the non-use of agrochemicals is enough to produce positive changes in soil fauna and so in decomposition dynamics. Therefore, the adoption of organic system in an extensive way can also be suggested to farmers in order to improve ecosystem functioning and consequently to achieve better soil conditions for crop production.